The use of generic and individual speed thresholds for assessing the competitive demands of field hockey - Casamichana, D.; Morencos, E.; Romero-Moraleda, B.; Gabbett, T. J. (Journal of Sports Science & Medicine, 2018)
The current study compared the running demands of professional field hockey players using individualized speed zones and generic default settings of the GPS manufacturer. In addition, the differences in slow, moderate and fast players were studied. Sixteen male players from the same club participated in the study (age: 25.5 ± 2.9 years; body mass: 74.6 ± 5.5 kg; stature 1.77 ± 0.05 m). The peak speed of each participant was established at the end of the data collection period by analyzing all training and playing data throughout the season. Using players peak speed achieved for each participant during the season, individualized speed zones were retrospectively applied to all match-play data. Peak speed was used to categorize players into three groups, slow (5 players: 29.2-30.2 km·h-1), moderate (6 players: 30.7-31.5 km·h-1) and fast (5 players: 32.2-33.7 km·h-1). Significant differences were observed between generic and individual thresholds for the distance covered in moderate, high, and very high-speed running in all positions (p = 0.01). Our findings show that the distances covered at high-speeds in midfielders and forwards were overestimated, while the very high-speed running and sprinting in backs were underestimated. Generic speed thresholds should be used if comparisons between positions is of importance. However, based on the different capacities of field hockey players, individual speed thresholds may be more suitable when addressing the relative stress on individual athletes.